Screen Time and Dry Eye Disease During Distance Learning among the Class of 2019 Medical Students at a University in Jakarta, Indonesia - Bernadette, Karen; Rasyid, Meriana (Folia Medica Indonesiana, 2023)
Highlights: • There is a correlation between screen time and dry eye disease among medical students due to distance learning during the pandemic. • This study's findings can lead researchers to conduct further studies to investigate and prevent DED. Abstract: Dry eye disease (DED), also known as dry-eye syndrome, is commonly caused by a lack of tears or excessive evaporation. It affects 334 million people worldwide. According to global epidemiological research, the DED prevalence in adults and the elderly is roughly 5-50%. Research has revealed that DED prevalence and epidemiology are more typically connected to aging. However, extended exposure to digital screens is an external DED risk factor to be aware of, especially in this digital technology era and amidst the COVID-19 pandemic. These two situations are expected to increase the number of DED sufferers in the younger age groups, such as elementary, high school, and university students. The ongoing COVID-19 pandemic has compelled a shift in learning and teaching methods in order for education to proceed. However, the digitization era and the COVID-19 pandemic can double the DED risk, particularly among medical students. This study's objective was to determine how remote learning affected DED prevalence among the class of 2019 medical students at Universitas Tarumanagara, Jakarta, Indonesia, in the COVID-19 pandemic. Data were collected from 144 respondents using a Google Forms questionnaire. According to the statistical test results, there was a 2.4-fold increase in screen time during the COVID-19 pandemic compared to the pre-pandemic period. The results demonstrated a significant relationship between screen time and DED among the class of 2019 medical students at Universitas Tarumanagara. These findings are predicted to be of interest to academics and students, as their frequent engagement with computer displays and smartphones will continue to increase due to technological advancements. Furthermore, researchers may use the findings as a reference in conducting DED-related research.